Under the world of AI-generated feedback on writing: mirroring motivation, foreign language peace of mind, trait emotional intelligence, and writing development - Shireen Jamal Mohammed; Maryam Waleed Khalid (Language Testing in Asia)
Abstract While over the last couple of years, there has been a growing investigation into the use of Artificial Intelligence (AI) within language learning, very little has been written regarding how such AI feedback influences the complex experiences of EFL learners in terms of motivation, foreign language peace of mind (FLPoM), trait emotional intelligence (EI), and writing proficiency. Therefore, this mixed method research inspected the impacts of AI-generated feedback on various aspects of English as a Foreign Language (EFL) learners’ experiences and skills, specifically focusing on motivation, FLPoM, EI, and writing proficiency in College of Languages, Nawroz University, Duhok, Kurdistan Region, Iraq. The research employed a quasi-experimental design with two groups: an experimental group (EG) engaged in online writing development with AI-generated feedback and a control group (CG) participating in the same online writing development without AI-generated feedback. Relevant and reliable scales were used as the pretest and posttest to measure changes in motivation, FLPoM, trait EI, and writing skills to assess the effects. The quantitative outcomes demonstrated that AI-generated feedback significantly improved EFL learners’ motivation, FLPoM, and trait EI while enhancing their writing skills. The qualitative findings (interview) showed that integrating AI-generated feedback into online writing instruction can substantially benefit EFL learners, offering a more supportive and effective learning context. The implications of the study point to the potential for AI to provide more personalized and supportive learning environments, matching a wide range of needs in language learners, thus encouraging further research into AI’s role in language education.